Clash of Identities: Ontological (In)Securities of Afghanistan and Pakistan, and the Repercussions. (16th November 2022) - Taj, Farhat
Abstract : The notion of security denotes freedom from threats. Ontological security implies emancipation from threats to core values that identify a person or a state. This article demonstrates the Pak-Afghan relationship as a case in point. It offers a relatively new perspective for understanding the continued contentious relationship between Afghanistan and Pakistan. It argues that the Pashtun state identity of Afghanistan mismatches with the Islamic identity of Pakistan. This causes cognitive anxiety over self-identity in both states, which confronts their respective ontological (in)security challenges. Consequently, both countries engage in dangerous routines of self-identity affirmation to manage their ontological (in)securities. The routines often have harmful consequences for the civilian population, especially in the Pashtun areas of Pakistan.